The Impact of Corporate Governance on Corporate Cash Holdings: A Comparative Study of the Manufacturing and Service Industry in UK - Agboola, Esther Damilola (2020)
This study investigates the impact of corporate governance on cash holdings from a comparative analysis of manufacturing and service sector using data spanning from 2011–2019 for 32 UK publicly listed firms on the FTSE 350 indices from each sector. Evidence shows that the relationship between companies’ corporate governance and cash holdings is dependent on their sectorial classification. The study measures corporate governance using two key indicators such as ownership structure and board characteristics (comprising of board gender and board independence). Using the GMM estimation, result shows that manufacturing sector depicts that there is a significant negative relationship between corporate governance and cash holdings. On the other hand, for the service sector, there is significant positive relationship between corporate governance and cash holdings. The differences in the major discoveries of the research evince that the pattern of cash holdings in the services sector varies significantly from the manufacturing sector, stemming from peculiarities in their operational needs. Likewise, considering the importance of firm-specific characteristics in driving the relationship that exist between these two variables (corporate governance and cash holdings), the study shows that firm-specific variables plays a significant role in determining the relationship between corporate governance and cash holdings for both manufacturing and service sector. Finally, the study recommends that firms in the manufacturing sector can maintain a low cash holding practice based on their easy access to the capital market; and firms in the service sector should utilize the excess cash in investment of profitable projects. Keywords: Corporate Governance, Cash Holdings, Ownership Structure, Board Independence, Board Gender, Firm Size, Dividends, Leverage, Liquidity Ratio